THE DYNAMICS OF ENERGY PRICE MOVEMENTS ESTIMATING COAL PRICE DYNAMICS WITH THE PRINCIPAL COMPONENTS METHOD - Festiđ, Mejra; Repina, Sebastijan; Kavkler, Alenka (Journal of Energy Technology, 2024)
Demand for energy resourcesis in creasing despiteef fort sat improvingen ergyefficiency. Coal constitutesonequarteroftotalprimaryenergyproduction. The future use of coaldependson environmental protection measures and the Kyoto Protocol. The price of coalisin fluenced by the price of coal production and preparation technologies, i.e. transportation costs, environmental legislation, the price of coalburning technologies, the price of gas purification, the price of CO 2 permissions or emission coupons, consumption, the price of other energy sources (naturalgasandoil) and the liberalizationof the electricity markets. We assessed the influence of prices and the use of other energy sources, environmental measures,energyefficiencyandtheinfluenceofelectricitymarketliberalisationoncoalprice movements. Our estimation shows that, if the prices of other energy sources and electricity increase, the price of coal increases. If the use of other energy sources increases, and if the gross uses of industrial waste and renewable resources increase, the price of coal decreases. Environmentalprotectionmeasurescontributetoanincreasein coal prices. Ahigherquotient of energy efficiency decelerates theprice of coal.Moreover, the euro(to dollar) appreciation decelerates coal prices.